2021
DOI: 10.1371/journal.pone.0249147
|View full text |Cite|
|
Sign up to set email alerts
|

Heavy metal accumulation by roadside vegetation and implications for pollution control

Abstract: Vehicular emissions cause heavy metal pollution and exert negative impacts on environment and roadside vegetation. Wild plants growing along roadsides are capable of absorbing considerable amounts of heavy metals; thus, could be helpful in reducing heavy metal pollution. Therefore, current study inferred heavy metal absorbance capacity of some wild plant species growing along roadside. Four different wild plant species, i.e., Acacia nilotica L., Calotropis procera L., Ricinus communis L., and Ziziphus mauritia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 82 publications
2
13
0
Order By: Relevance
“…In a study in the Kastmonu Province, Sevik et al ( 2020 ) proposed “edible landscaping”—strategic planting of certain fruit and vegetable trees, such as apple, plum, cherry, and mulberry, which can remove traffic-induced heavy metals (nickel, cobalt) from ambient air. Similar observations are widely reported from Pakistan (Altaf et al, 2020 ), Malaysia (Silaiman & Hamza, 2018 ), China (Qiu et al, 2009 ), and India (Rahul & Jain, 2016 ). In a case study involving traffic-induced heavy metal emissions (zinc, lead, chromium, and copper) in Bangalore City, India, Manjunath and Reddy ( 2019 ) observed that plants produced increased phenolic compounds (proline and malonaldehydes) to tolerate and mitigate oxidative stresses of air pollutants.…”
Section: Introductionsupporting
confidence: 85%
“…In a study in the Kastmonu Province, Sevik et al ( 2020 ) proposed “edible landscaping”—strategic planting of certain fruit and vegetable trees, such as apple, plum, cherry, and mulberry, which can remove traffic-induced heavy metals (nickel, cobalt) from ambient air. Similar observations are widely reported from Pakistan (Altaf et al, 2020 ), Malaysia (Silaiman & Hamza, 2018 ), China (Qiu et al, 2009 ), and India (Rahul & Jain, 2016 ). In a case study involving traffic-induced heavy metal emissions (zinc, lead, chromium, and copper) in Bangalore City, India, Manjunath and Reddy ( 2019 ) observed that plants produced increased phenolic compounds (proline and malonaldehydes) to tolerate and mitigate oxidative stresses of air pollutants.…”
Section: Introductionsupporting
confidence: 85%
“…Contamination of air, soil and water due to various kinds of pollutants which are byproduct of industrial activity has created a worldwide problem [1][2][3]. In recent years, heavy metals are the most important contaminants causing serious threat to the life of every living being.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above, roadside soil, street dust, and plants can be exposed to significant levels of metals, owing to both vehicle emissions and carried harmful chemicals [12][13][14]. The burning of fossil fuels, vehicle wear (tires, body and brakes) and vehicular fluids all contribute to increased metal levels in the environment [15]. It has been observed that roadside soil is highly contaminated with various heavy metals, namely Ni, Cd, Zn, Cu and Pb [12,13,16].…”
Section: Introductionmentioning
confidence: 99%